2014
DOI: 10.1074/jbc.m113.525576
|View full text |Cite
|
Sign up to set email alerts
|

An Internally Modulated, Thermostable, pH-sensitive Cys Loop Receptor from the Hydrothermal Vent Worm Alvinella pompejana

Abstract: Background: Cys loop receptors from the hydrothermal vent worm Alvinella pompejana were studied. Results: A Cys loop receptor opens at low pH, is chloride-specific, is modulated by its N-terminal extension, and is modestly thermostable. Conclusion: Cys loop receptors from worms living in extreme and secluded habitats are more closely related to eukaryotic than to prokaryotic family members. Significance: We studied the first known Cys loop receptor from a hydrothermal vent worm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 46 publications
5
9
0
Order By: Relevance
“…Moreover, we could confirm the activation of Alpo7-wt by elevated proton concentrations as previously described by Juneja, P. et al [27]. For Alpo1-wt, Alpo2-wt and Alpo4-wt none of the tested substances (Table 1) evoked channel activation.…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…Moreover, we could confirm the activation of Alpo7-wt by elevated proton concentrations as previously described by Juneja, P. et al [27]. For Alpo1-wt, Alpo2-wt and Alpo4-wt none of the tested substances (Table 1) evoked channel activation.…”
Section: Resultssupporting
confidence: 89%
“…to our nomenclature, Alv-a9 corresponds to Alpo1 and Alv-a1-pHCl corresponds to Alpo7. For Alv-a9 no activating ligand was found, whereas Alv-a1-pHCl is pH-activated [27], similar to ion channels found in other invertebrates [28]. In our study, we extended on these observations and identified five additional Alvinella pompejana CLR homologues.…”
Section: Introductionsupporting
confidence: 80%
See 3 more Smart Citations